Total synthesis of the endogenous inflammation resolving lipid resolvin D2 using a common lynchpin - Li, John; Leong, May May; Stewart, Alastair; Rizzacasa, Mark A. (Beilstein Journal of Organic Chemistry, 2013)
The total synthesis of the endogenous inflammation resolving eicosanoid resolvin D2 (1) is described. The key steps involved a Wittig reaction between aldehyde 5 and the ylide derived from phosphonium salt 6 to give enyne 17 and condensation of the same ylide with aldehyde 7 to afford enyne 11. Desilylation of 11 followed by hydrozirconation and iodination gave the vinyl iodide 4 and Sonogashira coupling between this compound and enyne 3 provided alkyne 18. Acetonide deprotection, partial reduction and ester hydrolysis then gave resolvin D2 (1).
Keywords: catalysis; eicosanoid; natural product; resolvin D2; Sonogashira coupling; total synthesis; Wittig reaction

(untitled) - Serhan, C. N.; Hong, S.; Gronert, K.; Colgan, S. P.; Devchand, P. R.; Mirick, G.; Moussignac, R.-L. (J. Exp. Med., 2002)

(untitled) - Serhan, C. N.; Petasis, N. A. (Chem. Rev., 2011)

(untitled) - Hong, S.; Gronert, K.; Devchand, P. R.; Moussignac, R.-L.; Serhan, C. N. (J. Biol. Chem., 2003)

(untitled) - Arita, M.; Bianchini, F.; Aliberti, J.; Sher, A.; Chiang, N.; Hong, S.; Yang, R.; Petasis, N. A.; Serhan, C. N. (J. Exp. Med., 2005)

(untitled) - Spite, M.; Norling, L. V.; Summers, L.; Yang, R.; Cooper, D.; Petasis, N. A.; Flower, R. J.; Perretti, M.; Serhan, C. N. (Nature, 2009)

(untitled) - Park, C.-K.; Xu, Z.-Z.; Liu, T.; Lü, N.; Serhan, C. N.; Ji, R.-R. (J. Neurosci., 2011)

(untitled) - Sun, Y.-P.; Oh, S. F.; Uddin, J.; Yang, R.; Gotlinger, K.; Campbell, E.; Colgan, S. P.; Petasis, N. A.; Serhan, C. N. (J. Biol. Chem., 2007)

(untitled) - Krishnamoorthy, S.; Recchiuti, A.; Chiang, N.; Yacoubian, S.; Lee, C.-H.; Yang, R.; Petasis, N. A.; Serhan, C. N. (Proc. Natl. Acad. Sci. U. S. A., 2010)

(untitled) - Rodríguez, A. R.; Spur, B. W. (Tetrahedron Lett., 2004)

(untitled) - Rodríguez, A. R.; Spur, B. W. (Tetrahedron Lett., 2012)

(untitled) - Winkler, J. W.; Uddin, J.; Serhan, C. N.; Petasis, N. A. (Org. Lett., 2013)

(untitled) - Rodríguez, A. R.; Spur, B. W. (Tetrahedron Lett., 2005)

(untitled) - Rodríguez, A. R.; Spur, B. W. (Tetrahedron Lett., 2012)

(untitled) - Ogawa, N.; Kobayashi, Y. (Tetrahedron Lett., 2009)

(untitled) - Allard, M.; Barnes, K.; Chen, X.; Cheung, Y.-Y.; Duffy, B.; Heap, C.; Inthavongsay, J.; Johnson, M.; Krishnamoorthy, R.; Manley, C.; Steffke, S.; Varughese, D.; et al. (Tetrahedron Lett., 2011)

(untitled) - Ogawa, S.; Urabe, D.; Yokokura, Y.; Arai, H.; Arita, M.; Inoue, M. (Org. Lett., 2009)

(untitled) - Kosaki, Y.; Ogawa, N.; Kobayashi, Y. (Tetrahedron Lett., 2010)

(untitled) - Urabe, D.; Todoroki, H.; Masuda, K.; Inoue, M. (Tetrahedron, 2012)

(untitled) - Amin, R.; Chen, J.-X.; Cotterill, I. C.; Emrich, D.; Ganley, D.; Khmelnitsky, Y. L.; McLaws, M. D.; Michels, P. C.; Schwartz, C. E.; Thomas, D.; Yan, J.; Yang, Q. (Org. Process Res. Dev., 2013)

(untitled) - Marshall, J. A.; Salovich, J. M.; Shearer, B. G. (J. Org. Chem., 1990)

(untitled) - Feutrill, J. T.; Lilly, M. J.; White, J. M.; Rizzacasa, M. A. (Tetrahedron, 2008)

(untitled) - Corey, E. J.; Marfat, A.; Munroe, J.; Kim, K. S.; Hopkins, P. B.; Brion, F. (Tetrahedron Lett., 1981)

(untitled) - Huang, Z.; Negishi, E.-i. (Org. Lett., 2006)

(untitled) - Sharpless, K. B.; Amberg, W.; Bennani, Y. L.; Crispino, G. A.; Hartung, J.; Jeong, K. S.; Kwong, H. L.; Morikawa, K.; Wang, Z. M. (J. Org. Chem., 1992)

(untitled) - Kolb, H. C.; VanNieuwenhze, M. S.; Sharpless, K. B. (Chem. Rev., 1994)

(untitled) - Rodríguez, A. R.; Spur, B. W. (Tetrahedron Lett., 2012)

(untitled) - Dale, J. A.; Mosher, H. S. (J. Am. Chem. Soc., 1973)

(untitled) - Hoye, T.; Jeffrey, C. S.; Shao, F. (Nat. Protoc., 2007)

(untitled) - Brown, C. A.; Ahuja, V. K. (J. Chem. Soc., Chem. Commun., 1973)

(untitled) - Rodríguez, A.; Nomen, M.; Spur, B. W.; Godfroid, J. J. (Tetrahedron Lett., 1999)

Comprehensive Organic Synthesis - Sonogashira, K. (Coupling Reactions Between sp2 and sp Carbon Centers, 1991)

(untitled) - Nicolaou, K. C.; Veale, C. A.; Webber, S. E.; Katerinopoulos, H. (J. Am. Chem. Soc., 1985)

(untitled) - Boland, W.; Schroer, N.; Sieler, C.; Feigel, M. (Helv. Chim. Acta, 1987)